Economic Interdependence: Evidence from China and ASEAN-5 Countries - Balasubramaniam, Arunnan; Puah, Chin Hong; Shazali, Abu Mansor (Scientific Research Publishing, 2012)
This study aimed to examine the interdependence relationship among five Association of Southeast Asian Nations (ASEAN-5) countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) and China from a business cycles perspective. The Granger non-causality test proposed by [1] was used to examine causal linkages in business cycles. The empirical results indicated common business cycles between China and ASEAN-5 economies. This suggested that China and ASEAN-5 share similar business cycles and could complement each other in the long run. A discussion of important insights for regional economic policy coordination in which similar business cycles provide a platform for common regional trade, as well as suggestions for monetary policies, conclude the paper.